2009
DOI: 10.1016/j.canlet.2009.03.024
|View full text |Cite
|
Sign up to set email alerts
|

ZBP-89 reduces the cell death threshold in hepatocellular carcinoma cells by increasing caspase-6 and S phase cell cycle arrest

Abstract: ZBP-89 inhibits the some tumor cells but its role in HCC is unknown. We investigated effect of ZBP-89 on cell death of 5 HCC cell lines with different status of p53. We found that ZBP-89 significantly induced cell death of all HCC cells particularly those with wild-type p53. The inhibition was well correlated with the induction of caspase-6 activity. The inhibition of caspase-6 abolished the effect of ZBP-89. ZBP-89 reduced the cells in G2-M but increased them in S phase. With the changes in caspase-6 and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…10 Moreover, overexpression of ZBP-89 is reported to significantly promote cell death in five HCC cell lines. 23 In line with the previous reports, our data showed that overexpression of ZBP-89 in HCC facilitated cell death induced by TSA via enhanced activation of Bid and PARP. However, overexpression of ZBP-89-Δ6-180 protein did not potentiate TSA-induced apoptosis, suggesting that the N terminus of ZBP-89 is essential for apoptosis induction.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…10 Moreover, overexpression of ZBP-89 is reported to significantly promote cell death in five HCC cell lines. 23 In line with the previous reports, our data showed that overexpression of ZBP-89 in HCC facilitated cell death induced by TSA via enhanced activation of Bid and PARP. However, overexpression of ZBP-89-Δ6-180 protein did not potentiate TSA-induced apoptosis, suggesting that the N terminus of ZBP-89 is essential for apoptosis induction.…”
Section: Discussionsupporting
confidence: 82%
“…We have previously reported that ZBP-89 overexpression resulted in apoptosis. 10,23 Using in situ cell death detection and TUNEL assays, we found that ectopic expression of ZBP-89 increased apoptosis ( Fig. 6A and B).…”
Section: Hdaci Induces Cell Cycle Arrest and Apoptosis In Hcc Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cell line has a mutation in the p53 gene that confers overexpression of p53 protein [16]. Overexpression of the tumor suppressor protein might be responsible for the greater cell damage induced by the chemotherapy and, consequently, the increased cell death [20,21]. …”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] ZNF148 is universally expressed at low levels in most tissues, 8 including those in the gastrointestinal tract. 9 ZNF148 is a multifunctional transcription factor associated with signaling pathways upstream of cellular proliferation, embryogenesis, differentiation, growth arrest, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%